Development and analysis of a numerical model of the reinforced concrete expansion by uniform corrosion - Felix, Emerson Felipe; Carrazedo, Rogério; Possan, Edna; Ramos, Everton Souza (Revista ALCONPAT, 2020)
This paper presents the modeling and analysis of the corrosion effects due to carbonation on reinforced concrete elements through a numerical model based on the Finite Element Method. In order to minimize corrosion damage, tools are required to understand the pathological manifestation on the mechanical behavior of reinforced concrete. It was found that depending on the reinforcement corrosion stage, the state of stress and deformation of the concrete element is compromised. Besides, results show the efficiency of the developed model and its applicability to the simulation of the mechanical behavior of reinforced concrete structures subjected to uniform corrosion.